Gastrointestinal microbiota and metabolites responses to dietary cereal grains in an adult pig model - Feng, Ganyi; Deng, Menglong; Li, Rui; Hou, Gaifeng; Ouyang, Qing; Jiang, Xianji; Liu, Xiaojie; Tang, Hui; Chen, Fengming; Pu, Shihua; Wan, Dan; Yin, Yulong (Frontiers in Microbiology, 2024)
Corn, wheat and paddy rice are important energy sources and commonly used in feed production for swine. This study mainly focuses on the variation regularities of microbiota and metabolites in gastrointestinal tract (GIT) of pigs in response to corn, wheat and paddy rice. Eighteen pigs were allotted into three dietary groups with 6 replicated pigs, and received diets containing corn, wheat or paddy rice as the sole energy source, respectively. Results showed that digestive parts significantly affected the diversity of microbial communities. Cereal grains sources significantly influenced the βdiversity of microbial communities in the colon and rectum. Campliobacterota and Proteobacteria mainly distributed in duodenum, Lactobacillus in jejunum, and Bacteroidota in colon and rectum. Wheat diet increased the Bacteroidota, Spirnochaetota and Prevotellaceae_NK3B31_group abundances, and showed highest concentrations of all short-chain fatty acids (SCFAs) in the hindgut. Fibrobacterota, Bacteroidota, Spirochaetota, Prevotellaceae_NK3B31_group, Prevotella and Treponema in the colon or rectum were positively correlated with acetate, propionate, butyrate and total SCFAs. These findings suggested that aerobic bacteria and facultative anaerobe in the foregut will gradually be replaced by anaerobe in the hindgut. Wheat diet had the best fermentability, and was beneficial to the colonization of microbial communities that mainly used carbohydrates. The hindgut flora of paddy rice diet group may be more balanced with less potential pathogenic bacteria. Many microbial communities have been identified to contribute positively to the SCFAs production of the hindgut. Collectively, our study revealed the spatial variation regularities of GIT microbial communities in adult pig model, and provided new insights for GIT microbiota and metabolites responses to cereal grains diets.